Children with Cerebral Palsy and their Quality Of Life in Nepal - Shrestha, Niti; Paudel, Sabitra; Thapa, Ritesh (Journal of Nepal Paediatric Society, 2018)
Introduction: Cerebral Palsy (CP) may affect individual’s everyday life and it may have significant impact on quality of life (QOL). The objective of this study was to assess the quality of life of children with Cerebral Palsy in Nepal. Material and Methods: This is a descriptive cross sectional study that involved 42 children between 4 and 12 years of age. The Socio-demographic variables were obtained from interviews and CP related factors were obtained from medical reports. Validated CP-QOL child self-report and parent proxy version of questionnaire was used for data collection. Severity was assessed using Gross Motor Function Classification System (GMFCS), Manual Ability Classification System (MACS), Communication function Classification System (CFCS) and ICD-10 Classification System. Data were summarized using descriptive statistics. Kruskal Wallis and Man Whitney was used to find out association between Cerebral Palsy related factors and Quality of Life. Results: 57.1% (n=24) were between 8 and12 years of age and 42.9% (n=18) were between 4 and 8 years of age. Overall QOL was reported to be fairly good. Both the child and Caregiver gave highest score on “Social wellbeing and acceptance” and “Emotional wellbeing and self-esteem domain” and Lowest Point in “Pain and Impact of disability”. This implies that Psychosocial Quality of Life is good in children with CP. Quality of Life as reported by child was better than Quality of Life reported by Caregiver. Conclusion: Overall QOL is fairly good in children with CP. However, Pain and impact of disability impairs QOL.